2019
DOI: 10.1108/prr-12-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between human resource management practices, ethical climates and organizational performance, the missing link

Abstract: Purpose The purpose of this paper is to investigate the influence of human resource management (HRM) practices, (recruitment and selection) and organizational performance (OP) through mediation role of ethical climates (ECs) in Nigerian educational agencies. Design/methodology/approach Quantitative data were collected from 181 educational agencies represented by director of administration; SmartPLS-SEM was used in testing the relationship, as well as testing the mediating effect of ECs. Findings The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 78 publications
0
18
0
3
Order By: Relevance
“…For example, Haverila and Haverila [70] used PLS-SEM and SmartPLS software to study customer perceptions of project management performance. Sabiu et al [71] used SmartPLS-SEM to test the relationship between human resource management practices (recruitment and selection) and organizational performance. Numerous studies have shown SmartPLS-SEM can be applicable for studies in consumer preference for e-commerce overpackaging solutions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Haverila and Haverila [70] used PLS-SEM and SmartPLS software to study customer perceptions of project management performance. Sabiu et al [71] used SmartPLS-SEM to test the relationship between human resource management practices (recruitment and selection) and organizational performance. Numerous studies have shown SmartPLS-SEM can be applicable for studies in consumer preference for e-commerce overpackaging solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Manajemen sumber daya manusia (MSDM) didefinisikan sebagai proses mendapatkan, mengembangkan, dan memelihara karyawan (Armstrong & Taylor, 2014). Dengan demikian, praktek MSDM didefinisikan sebagai kebijakan dan kegiatan manajerial yang bertujuan untuk meningkatkan kontribusi produktif karyawan kepada organisasi Sabiu et al (2019) berpendapat bahwa MSDM adalah kunci pengembangan organisasi dan karyawan. Praktek MSDM bertujuan untuk meningkatkan kontribusi karyawan terhadap kinerja perusahaan.…”
Section: Pengaruh Praktek Msdm Terhadap Kinerja Organisasiunclassified
“…However, generally, in the formal method, it is conducted by the immediate manager or supervisor under whom the person is directly working. A performance appraisal is a part of measuring, comparing, finding, guiding, correcting, and managing the employees (Sabiu et al, 2019).…”
Section: Performance Appraisalmentioning
confidence: 99%